The Regulation of AMPA Receptor Endocytosis by Dynamic Protein-Protein Interactions - Hanley, Jonathan G. (Frontiers in Cellular Neuroscience, 2018)
The precise regulation of AMPA receptor (AMPAR) trafficking in neurons is crucial for excitatory neurotransmission, synaptic plasticity and the consequent formation and modification of neural circuits during brain development and learning. Clathrin-mediated endocytosis is an essential trafficking event for the activity-dependent removal of AMPARs from the neuronal plasma membrane, resulting in a reduction in synaptic strength known as Long-Term Depression (LTD). The regulated AMPAR endocytosis that underlies LTD is caused by specific modes of synaptic activity, most notably stimulation of NMDARs and mGluRs. Numerous proteins associate with AMPAR subunits, directly or indirectly, to control their trafficking, and therefore the regulation of these protein-protein interactions in response to NMDAR or mGluR signalling is a critical feature of synaptic plasticity. In this paper, we review the protein-protein interactions that are dynamically regulated during synaptic plasticity to modulate AMPAR endocytosis, focussing on AMPAR binding proteins and proteins that bind the core endocytic machinery. We consider the mechanisms for the regulation of protein binding, and also the functional consequences of these dynamic interactions on AMPAR endocytosis.